DETERMINANTS OF CONSUMER INTENTION IN USING DIGITAL PAYMENT: THE ROLE OF USER SATISFACTION AMONG MILLENNIALS IN URBAN AREAS - Dhevi Dadi Kusumaningtyas; Luthfy Purnanta Anzie; Eirene Ivane Santoso; Nur Aissyah (ITB AAS Indonesia Surakarta, 2025)
Digital payment offers great flexibility in shopping at any time or place via embedding into a series of e-commerce sites and mobile applications. A quantitative design with correlational methodology is followed in the present study. This paper seeks to examine the influence of digital payment on user intention through the mediating effect of satisfaction in millennial generation. The samples were determined by purposive sampling technique to 100 respondents who are millennial generation living in the urban area of Central Java. A questionnaire and a Likert scale were used to gathered research data. In analyzing the data process, its use path analysis and test of data helped by SmartPLS software version 4.1.1.2. Path analysis consists of two parts, the outer model and the inner model. The findings indicated that digital payment was confirmed to have a positive effect on user satisfaction. The next direct effect, the digital payment, was a positive significant impact on consumer intention. Additionally, the user satisfaction variable was found to exert a significant positive influence on consumer intention. In the other hand, the user satisfaction dimension was confirmed as capable of mediating between digital payment and consumer intention.